Understanding the Well-Being of Older Chinese Immigrants in Relation to Green Spaces: A Gold Coast Study (Australia) - Gao, Siyao; Bosman, Caryl; Dupre, Karine (Frontiers in Psychology, 2020)
In recognition of the aging population and the importance of health-supporting urban environments, including urban green spaces, to maintain well-being, scholars and policymakers have increasingly investigated the associations between urban green spaces and the well-being of older people. However, few studies specifically investigate minority older groups such as those with diverse cultural backgrounds, and many studies often ignore the design attributes of green spaces which may contribute to the well-being of those in such groups. In order to address these gaps, this paper explores how green spaces influence the well-being of older Chinese immigrants. This case study analyzes how older Chinese immigrants interact with green spaces on the Gold Coast, Australia, and adopts the value of place as a conceptual framework to understand the relationship. Two qualitative methods, namely, in-depth interviews and travel diaries, were used to collect data. The results show that parks, as a place, play a crucial role in older Chinese immigrants’ ability to undertake outdoor activities. The relationship between green spaces and well-being can be classified into two themes. The first theme is concerned with how older Chinese immigrants perceive and experience green spaces. This finding indicates that green spaces can fulfill their values of keeping healthy, maintaining active lifestyles, and being social, all of which benefit well-being. The second theme relates to daily activities undertaken within green spaces. Issues of accessibility and personal preferences regarding activities complicate the relationship between green spaces and well-being. Good accessibility to green spaces is congruent with older Chinese immigrants’ values of being physically active, while difficulties in conducting preferred activities counteract these values which then generate negative perceptions of green spaces. Overall, there is great potential for understanding how personal values can inform the design of inclusive green spaces for minority or less mobile groups.